BROMINATION REALITIES of 2,4-DIHYDROXYACETOPHENONE AND ITS DERIVATIVES: UDC 547.571 (Bulletin of the Taras Shevchenko National University of Kyiv. Chemistry, 2017)
Bromination process of resacetophenone was studied in a wide range of conditions – the heterogeneous bromination with CuBr2 and photochemical bromination with N-bromosuccinimide (NBS) in various solvents with an initiator and in the absence thereof. It is shown that under all these conditions, the bromination of resacetophenone passes not selectively, mainly in the nucleus, but not in the side chain, to form a mixture of different bromo derivatives, that have been identified by the aid of 1H NMR spectroscopy. Exactly the presence of two hydroxyl groups in the structure of the resacetophenone defines the direction of the bromination process. It is necessary to eliminate the influence of these groups for selective bromination of the resacetophenone side chain. The elimination of the influence of hydroxyl groups may be achieved by blockind them, for example, by their alkylation or benzylation. Examples of selective α-bromination of alkoxy and benzyloxy resacetophenone derivatives were described in the literature, but as it is known the subsequent process of removing the blocking and transition to the α-bromo-2,4-dihydroxyacetophenone often proves quite problematic. The bromination process of resacetophenone 2,4-diacetoxy and 2-hydroxy-4-acetoxy derivatives were explored. It was found that both the heterogeneous bromination with CuBr2 and the photochemical bromination with NBS in the ether of 2,4-diacetoxyacetophenone held in α-position to the carbonyl group with simultaneous deacylation to give α-bromo-2,4-dihydroxyacetophenone. but in the case of photochemical bromination desired α-bromo-2,4-dihydroxyacetophenone is formed in admixture with resacetophenone in a ratio of 1 to 3.The heterogeneous bromination with CuBr2 of 2-hydroxy-4-acetoxyacetophenone held in α-position to the carbonyl group with simultaneous deacylation to give α-bromo-2,4-dihydroxyacetophenone in admixture with resacetophenone in a ratio of 1 to 0,75.
Keywords: heterogeneous bromination CuBr2; photochemical bromination with N-bromosuccinimide; 5-bromo-2,4-dihydroxyacetophenone; 3-bromo-2,4-dihydroxyacetophenone; 3,5-dibromo-2,4-dihydroxyacetophenone; α-bromo-2,4-dihydroxyacetophenone; α-bromo-2,4-dihydroxy-5-bromoacetophenone